Use of humour in medical education: a survey of students and teachers at a medical school in China. Issue 11 (28th November 2017) - Liu, Yan-Ping; Sun, Lei; Wu, Xiao-Fen; Yang, Yi; Zhang, Cun-Tai; Zhou, Hong-Lian; Quan, Xiao-Qing
Abstract : Objective: Humour is a powerful resource in medical education. The purpose of this study is to investigate what students and teachers think about the use of humour. What challenges do teachers face in using humour and how they address them are also the subject of the present study. Design: Separate cross-sectional questionnaire surveys. Setting: Tongji Medical College and Tongji Hospital in China. Participants: 327 students at Tongji Medical College and 165 physician teachers at Tongji Hospital in China. Main outcome measures: The primary study outcome was assessed by proportion. Results: 87% of student and teacher respondents agreed with using humour in the didactic setting. They felt humour fostered a positive didactic atmosphere. Interesting clinical case was the most frequently used humour type by teachers and considered the most effective by students. Lack of humorous materials related to the lecture subject was the main challenge to humour use cited by teachers. Collecting humorous materials in teacher's daily work and life, observing teachers with a reputation for successfully using humour, and efficiently using the internet-enhanced humour use ability. Conclusion: The present study confirms that most medical students and physician teachers support the use of humour in medical didactics, with particular strategies aiding its use and positive impact.